Exposure of the heart in lung cancer radiation therapy: A systematic review of heart doses published during 2013 to 2020. (July 2022) - Kearney, Maeve; Keys, Maeve; Faivre-Finn, Corinne; Wang, Zhe; Aznar, Marianne C; Duane, Frances
Highlights: Cardiac exposure from IMRT is similar to 3DCRT using current optimisation objectives. More stringent IMRT cardiac sparing planning objectives may reduce cardiac exposure. Consensus on contouring and Dose Volume Constraints for the heart is lacking. Dose parameters reported for cardiac substructures, pericardium and the great vessels vary substantially. Further heart sparing may be achieved using active respiratory motion management or particle beam therapy. Abstract: Background and purpose: Lung cancer radiotherapy increases the risk of cardiotoxicity and heart radiation dose is an independent predictor of poor survival. This study describes heart doses and strategies aiming to reduce exposure. Materials and methods: A systematic review of lung cancer dosimetry studies reporting heart doses published 2013–2020 was undertaken. Doses were compared according to laterality, region irradiated, treatment modality (stereotactic ablative body radiotherapy (SABR) and non-SABR), planning technique, and respiratory motion management. Results: For 392 non-SABR regimens in 105 studies, the average MHD was 10.3 Gy (0.0–48.4) and was not significantly different between left and right-sided tumours. It was similar between IMRT and 3DCRT (10.9 Gy versus 10.6 Gy) and lower with particle beam therapy (proton 7.0 Gy; carbon-ion 1.9 Gy). Active respiratory motion management reduced exposure (7.4 Gy versus 9.3 Gy). For 168 SABR regimens in 35 studies, MHD was 4.0 Gy (0.0–32.4). Exposure was higher in central and lower lobe lesions (6.3 and 5.8 Gy respectively). MHD was lowest for carbon ions (0.5 Gy) compared to other techniques. Active respiratory motion management reduced exposure (2.4 Gy versus 5.0 Gy). Delineation guidelines and Dose Volume Constraints for the heart varied substantially. Conclusions: There is scope to reduce heart radiation dose in lung cancer radiotherapy. Consensus on planning objectives, contouring and DVCs for the heart may lead to reduced heart doses in the future. For IMRT, more stringent optimisation objectives may reduce heart dose. Active respiratory motion management or particle therapy may be considered in situations where cardiac dose is high.